Leaf Trichome Morphology of Durio Kutejensis Landraces from Kalimantan - Priyanti,; Chikmawati, Tatik; Sobir,; Hartana, Alex (Makara Journal of Science, 2015)
The leaf trichome morphology of 19 Durio kutejensis (lai) landraces was studied. The observation of cross- and paradermal sections of D. kutejensis leaves showed that all landraces have glabrous leaves on the adaxial surface, while their abaxial surfaces are covered by six trichome types, one glandular (one- or two-celled stalks with a spheroid multicellular glandular head) and five non-glandular (complex peltate, simple peltate, cushioned stellate, flat stellate, and four-armed stellate trichome with a central cushion). All landraces were rarely covered by glandular trichomes. The non-glandular trichomes are varied in type, density, number of layers, diameter, and shape and margin color of the complex peltate among landraces. One landrace comprises three non-glandular trichome types, while the other landraces consist of four or five non-glandular trichome types. The shapes and margin color of complex peltate trichomes of D. kutejensis are the specific characteristics which distinguish this species from the other Durio species, however these characteristics cannot be used to differentiate one D. kutejensis landraces from the other. Therefore, other characteristics need to be explored in order to distinguish one D. kutejensis landraces from the other.